EFFECT OF DIFFERENT SCHEDULES OF VACCINES ON GROWTH AND PERFORMANCE OF BROILERS - RAUF, U; HAQ, SU; ARSHAD, Z; USMAN, M; SAJID, M; WAHEED, SF; HUSSAIN, T; HUSSAIN, A; AMEER, S; NAZEER, HAA; et al. (Biological and Clinical Sciences Research Journal, 2024)
A vaccination program is a schedule of vaccinations that varies by nation or property. This study set out to assess the productivity and overall health of broiler chickens with different immunization schedules. From a total of 110 Cobb 500 chickens, three treatment groups—each with six duplicates—were chosen at random. For every treatment group, there were different immunization schedules for Newcastle disease, infectious bronchitis, and infectious bursal disease. On the other hand, broilers in Treatment 2 (T2) received vaccinations against ND+IB on days 3 and 7, whereas broilers in Treatment 3 (T3) received vaccinations against ND+IB on days 7 and 21 as well as IBD on day 14. The grill control group in treatment 1 (T1) was vaccinated against ND+IB and IBD on days 7 and 14, respectively. During the 42-day study period, samples and data were gathered to evaluate the animals’ development performance, immunological status, carcass characteristics, and meat quality. T1 broilers fared better than T2 and T3 broilers in terms of growth rate, white blood cell count, carcase features, and meat quality. The results of this study show that immunizing broilers against ND+IB and IBD on days 7 and 14 is the most successful vaccination schedule for broiler production, as demonstrated by the animals’ improved health and productivity.